2018
DOI: 10.1021/acs.bioconjchem.8b00354
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Amphiphilic Proteins to Hydrophobic Ligands in Organic Solvent

Abstract: Protein-ligand conjugations are usually carried out in aqueous media in order to mimic the environment within which the conjugates will be used. In this work, we focus on the conjugation of amphiphilic variants of elastin-like polypeptide (ELP), short elastin (sEL), to poorly water-soluble compounds like OPPVs ( p-phenylenevinylene oligomers), triarylamines, and polypyridine-metal complexes. These conjugations are problematic when carried out in aqueous phase because hydrophobic ligands tend to avoid exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
(114 reference statements)
0
8
0
Order By: Relevance
“…Russell et al have investigated chymotrypsin-poly­(2-(dimethylamino)­ethyl methacrylate) (CT-pDMAEMA) solubility and activity in acetonitrile . Protein–polymer conjugate synthesis has also been performed in organic solvent in order to increase the conjugation yield of an amphiphilic protein to a hydrophobic ligand (or polymer) . Moreover, Thayumanavan et al found that polymeric supramolecular assemblies could help efficiently transport proteins from an aqueous phase to an organic phase .…”
Section: Protein–polymer Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Russell et al have investigated chymotrypsin-poly­(2-(dimethylamino)­ethyl methacrylate) (CT-pDMAEMA) solubility and activity in acetonitrile . Protein–polymer conjugate synthesis has also been performed in organic solvent in order to increase the conjugation yield of an amphiphilic protein to a hydrophobic ligand (or polymer) . Moreover, Thayumanavan et al found that polymeric supramolecular assemblies could help efficiently transport proteins from an aqueous phase to an organic phase .…”
Section: Protein–polymer Conjugatesmentioning
confidence: 99%
“…103 Protein−polymer conjugate synthesis has also been performed in organic solvent in order to increase the conjugation yield of an amphiphilic protein to a hydrophobic ligand (or polymer). 104 Moreover, Thayumanavan et al found that polymeric supramolecular assemblies could help efficiently transport proteins from an aqueous phase to an organic phase. 105 Ionic liquids are another class of nonaqueous media that are attractive because they are nonvolatile, more environmentally friendly, and have tunable properties.…”
Section: ■ Protein−polymer Conjugatesmentioning
confidence: 99%
“…The chemical stability (e.g., against thermal stress) of proteins has also been improved by modification with polysaccharides, which are hydrophilic groups [ 9 , 10 , 11 ]. The chemical modification of proteins has mostly been via conjugation with hydrophilic groups, but there are a few reports on chemical modification using hydrophobic groups [ 12 , 13 ]. Chemical modification of hydrophobic groups to water soluble polymers has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear-magnetic resonance (NMR) and13 C NMR spectra of CHLysozyme in DMSO-d6 at 25 °C. (a) 1 H NMR spectrum, and (b)13 C NMR spectrum, CHLysozyme concentration: 21.4 mg/mL.…”
mentioning
confidence: 99%
“…10−12 Although most proteins are modified with hydrophilic groups, some studies have introduced modifications with hydrophobic groups. 13,14 In natively structured proteins, hydrophobic residues are burried; 15,16 however, protein denaturation, induced by physical stress, heat, or chemical exposure, allows these residues to become exposed. 13,17−19 Aggregation of proteins is mediated by hydrophobic interactions between the newly exposed hydrophobic residues of denatured proteins.…”
Section: Introductionmentioning
confidence: 99%